Processo participativo de planejamento estratégico : a experiência da Empresa Gráfica da Bahia - EGBA - Silva, Manoel Vitório da (2006)
This Dissertation is consisted in a case study tends as object the Empresa Gráfica da Bahia (EGBA) that, starting from 1997, it Term of Commitment of Administration with the Government of the State of Bahia, and in a modernization process and the employees' motivation, it got to increase the productivity and to guarantee the solemnity-sustenance. The Term of Commitment foresaw the period of two years for the obtain of the goals, but these were obtained starting from the year of 1997, and as consequence EGBA became market regulator and services offering to the State, with price reduction for this of 59,26% in relation to the market and for the private customers a reduction of prices that varied between 5 and 10%. In that process, was identified a high motivation of the employees, with the reduction of 69% of the lacks to the non justified work and the increase of productivity of 13%. That research intends to contribute, for the development of studies, on the process of participation, in the introduction of the strategic planning in the organizations.